Adolescent food intake: Validation and calibration of a food frequency questionnaire in a complex sampling study (Research, Society and Development, 2021)
Studies on dietary patterns depend on the validity of methods, such as the food frequency questionnaire (FFQ), to estimate long-term food intake, which can be overestimated, and the method needs to be validated. It is questioned whether validation studies nested in studies with complex sample design (CSD) should ignore data dependence. This study aims to validate the FFQ applied to school adolescents and estimate the calibration factors in a study with complex sampling. The validity of the FFQ is tested against dietary records (DR) applied to 85 adolescents in a study with CSD, with estimation of calibration factors (λ) for energy, nutrients, and dietary groups (DG). Intraclass correlation coefficient was calculated; mean differences were compared by modeling, and agreement analyzes were performed. The means between the methods differed for energy and nutrients (p